2019
DOI: 10.1186/s13148-019-0774-2
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic therapy of novel tumour suppressor ZAR1 and its cancer biomarker function

Abstract: BackgroundCancer still is one of the leading causes of death and its death toll is predicted to rise further. We identified earlier the potential tumour suppressor zygote arrest 1 (ZAR1) to play a role in lung carcinogenesis through its epigenetic inactivation.ResultsWe are the first to report that ZAR1 is epigenetically inactivated not only in lung cancer but also across cancer types, and ZAR1 methylation occurs across its complete CpG island. ZAR1 hypermethylation significantly correlates with its expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 88 publications
3
11
0
Order By: Relevance
“…The basis for our simulation were 758,289 mean and standard deviation values from probes on an EPIC array, based on data from 69 patients collected in our laboratory. 1 Based on this data, random numbers were generated from a normal distribution using the "rnorm" function with the "Mersenne-Twister" algorithm [24] to generate simulated methylation beta values for every CpG site with a mean and standard deviation corresponding to the natural CpG sites. 2 Data from our laboratory were not used in any further analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The basis for our simulation were 758,289 mean and standard deviation values from probes on an EPIC array, based on data from 69 patients collected in our laboratory. 1 Based on this data, random numbers were generated from a normal distribution using the "rnorm" function with the "Mersenne-Twister" algorithm [24] to generate simulated methylation beta values for every CpG site with a mean and standard deviation corresponding to the natural CpG sites. 2 Data from our laboratory were not used in any further analyses.…”
Section: Methodsmentioning
confidence: 99%
“…In the last two decades, the field of epigenetics has opened up new perspectives on complex medical questions [1][2][3]. DNA methylation (DNAm) is assumed to be modulated both by heritable factors [4] and by environmental conditions [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…IRX1 RNA guides for promotor reporter assay are #1, #3 CGCGACCGGCCTCCATC (−166), #5 TTGCCGGTCTGGCGGCGGCGC (-1201), and #6 GAGAAGAGGGACGCGGGACT (positioned -1242). p300 (pcDNA-dCas9-p300 Core, Addgene, Watertown, USA) was used as epigenetic modifier upon co-transfection in HeLa cells [64].…”
Section: Genetic and Epigenetic Editingmentioning
confidence: 99%
“…Zar1 was first observed in mice during oocyte to embryo transition, and Zar1 double knockout mice are infertile (X. Wu et al, 2003). In the context of cancer, it is a tumor suppressor that is found to be strongly hypermethylated in lung and kidney cancer and serves as an excellent diagnostic marker (Deutschmeyer et al, 2019). Here, the authors showed that ZAR1 expression correlated with TP53 (tumor protein p53) signaling pathway and G2M cell cycle checkpoint, which was a zinc finger motif‐dependent.…”
Section: Regulation Of Pb Components By Epigenetic Machinery and Theimentioning
confidence: 99%
“…In corroboration with this study, Richter et al (2017) showed that ZAR1 is hypermethylated in primary lung cancer samples (22% small‐cell lung carcinoma and 76% non‐small‐cell lung carcinoma) whereas normal lung tissues were hypermethylated at only 11% (Figure 3; Table 2). A study also showed using the CRISPR‐CAS9 system that Zar1 can be edited and reactivated (Deutschmeyer et al, 2019). This study implies the therapeutic role of ZAR1.…”
Section: Regulation Of Pb Components By Epigenetic Machinery and Theimentioning
confidence: 99%